AUDIT OF INFORMATION SYSTEM USING COBIT 5.0 AND ITIL V3 FOR INFORMATION SYSTEM OF ACADEMIC - Listiani, Rini Nur; Aziz, R.Z Abdul (Prosiding International conference on Information Technology and Business (ICITB), 2018)
Information Technology (IT) is very important for sustainability and business growth. Dependence on IT requires special attention to governance which consists of leadership, organizational structure, and processes. it ensure that IT in the organization not only develops, but also sustains the company's strategy and goals. Informatics and Business Institute Darmajaya is one of the private universities in Bandar Lampung that utilizes IT in carrying out academic activities, one of which is by using the Information System of Academic (SISKA). In the implementation of good SISKA, an audit of information system needed to improve the performance of the system. In this study, audit for information system of academic used Control Objective for Information and related Technology (COBIT 5.0) on domains DSS01-DSS06, MEA-01, APO-12, and APO-13, as well as other references to determine improvement suggestions by adding the Information Processing Infrastructure Library (ITIL V3) on the domain process of Service Operation and Service Design processes as a framework. This study was used to evaluate the governance information systems of academic at Darmajaya to produce some recommendations for improvement. The results was used to provide recommendations for improvements to the information technology governance of SISKA IIB Darmajaya. For measure, this study using addition validity and reliability with SPSS tools to testing produce appropriate improvements for IT governance.Keywords: Audit of Information System, COBIT 5.0, ITIL V3, IT Governance.